Hallyu Tsunami: How Korean Pop Culture is Reshaping Indonesian Consumer - Lintang Calavera Hening; Meissy Kristine Toding; Muhammad Hisyam Sabbil (LATTE: A Journal of Language, Culture, and Technology ISSN 3063-0754, 2024)
The global phenomenon known as Hallyu or the Korean Wave has a significant impact on many facets of culture and society. Due to the worldwide impact of Korean pop culture, Indonesia, one of the nations most affected by this cultural wave, has seen notable changes in consumer behavior. In addition to winning over Indonesian consumers' hearts, the Hallyu phenomenon has drastically changed their consumption habits, taste in food, fashion and way of life. Keywords: Korean wave, pop culture, hallyu, culture, Indonesian consumers, mass culture, soft power.